Assessment of Behavioral Intention to Adopt Educational Mobile Application in Advanced Mathematics for Engineering Education - Novesteras, Aura Marie (Journal of Interdisciplinary Perspectives, 2024)
Technology has long played a crucial role in society, including its application in education. The learning experiences of students in higher education have been significantly transformed. This study explores the adoption and acceptance of the Advanced Math mobile application among students, focusing on four key variables: social influence, performance expectancy, effort expectancy, and facilitating conditions. The study involved 253 participants who downloaded and used the Advanced Math mobile application as a supplemental study tool. The findings indicate that social influence significantly impacts students' decisions to use the application. The performance of the mobile application enhances students' productivity by providing easy access to lecture information, thereby supporting their learning process and motivating them to use the application. Facilitating conditions enable students to work independently at their preferred pace and access the application anytime and anywhere. The behavioral intention to use the mobile application is associated with positive feelings, leading students to use it as an additional resource for learning Advanced Math. Mobile applications have the potential to revolutionize educational settings by enhancing engagement, accessibility, and personalized learning. However, their effective use in the classroom necessitates robust pedagogical frameworks that align with learning objectives and provide continuous support for educators. Future research should continue to explore the challenges and opportunities of integrating mobile applications into the classroom to support both teachers and students in an increasingly digital society.